Reading in Healthy Aging: Selective Use of Information Structuring Cues. Issue 2 (17th February 2018) - Price, Jessica M.; Sanford, Anthony J.
ABSTRACT: Previous research has shown that information referring to a named character or to information in the main clause of a sentence is more accessible and facilitates the processing of anaphoric references. We investigated whether the use of such cues are maintained in healthy aging. We present two experiments investigating whether information contained in the main clause of a sentence is more accessible compared with information contained in the subordinate clause. We present two further experiments that explored whether proper names act as controllers of discourse focus. Experiment 1 showed that information contained in the subordinate clause of a sentence decreased the processing efficiency of anaphoric references (more so for older adults), and Experiment 2 found that main clauses facilitated probe recognition. Experiments 3 and 4 showed that named characters increased the processing efficiency of anaphoric references and facilitated probe recognition (younger adults only), whereas older adults displayed a primacy effect.